2009
DOI: 10.1111/j.1365-2044.2008.05786.x
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the utility of C‐reactive protein in predicting early, intermediate‐term and long term mortality and major adverse cardiac events in vascular surgical patients

Abstract: SummaryWe conducted a meta-analysis of the utility of pre-operative C reactive protein (CRP) in predicting early (< 30 days), intermediate (30-180 days) and long term (> 180 days) mortality and major adverse cardiac events (MACE; cardiac mortality and nonfatal myocardial infarction (MI) combined) following vascular surgery. Of 291 studies identified, ten prospective patient cohorts were identified. A pre-operative CRP > 3 mg. Vascular surgery is associated with major adverse perioperative cardiac events. Unfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 36 publications
0
16
0
2
Order By: Relevance
“…Before surgery, several inflammatory markers haven shown prognostic value in HF including tumour necrosis factor and its receptors, the interleukin (IL)‐1 and IL‐6 families, galectin‐3, and C‐reactive protein 3, 4. Besides, increased inflammation before cardiac surgery with cardiopulmonary bypass is associated with worse outcome 5, 6. After surgery, graft inflammation may respond to several mechanisms, from alloantigen‐directed immune reactions of the recipient resulting in graft rejection to ischaemia/reperfusion injury of the graft 7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before surgery, several inflammatory markers haven shown prognostic value in HF including tumour necrosis factor and its receptors, the interleukin (IL)‐1 and IL‐6 families, galectin‐3, and C‐reactive protein 3, 4. Besides, increased inflammation before cardiac surgery with cardiopulmonary bypass is associated with worse outcome 5, 6. After surgery, graft inflammation may respond to several mechanisms, from alloantigen‐directed immune reactions of the recipient resulting in graft rejection to ischaemia/reperfusion injury of the graft 7.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Besides, increased inflammation before cardiac surgery with cardiopulmonary bypass is associated with worse outcome. 5,6 After surgery, graft inflammation may respond to several mechanisms, from alloantigen-directed immune reactions of the recipient resulting in graft rejection to ischaemia/reperfusion injury of the graft. 7 Inflammation of the donor before explantation is also associated with worse outcome of the recipient.…”
Section: Introductionmentioning
confidence: 99%
“…However, C-reactive protein levels were higher in those who lost weight. High C-reactive protein, as a positive acute phase reactant suggests a proinflammatory state 27. Although not specifically examined here, C-reactive protein and other biomarkers of inflammation may well have utility in signaling the potential for more adverse health outcomes in elderly women.…”
Section: Discussionmentioning
confidence: 96%
“…1 C-reactive protein (CRP) and NT-pro-brain natriuretic peptide (BNP) have been associated with increased mortality after vascular surgery. [2][3][4][5][6][7] Several large-scale population studies have demonstrated that CRP profiling has improved the prediction of the first cardiovascular event. [8][9][10] The use of proteomic tools to create molecular signatures of disease is a recent development in the domain of disease diagnostics.…”
Section: Introductionmentioning
confidence: 99%